Experimental study on Zhundong coal gasification in supercritical water with a quartz reactor: Reaction kinetics and pathway. (29th June 2015) - Su, Xiaohui; Jin, Hui; Guo, Liejin; Guo, Simao; Ge, Zhiwei
Abstract China has fairly rich reserves of Zhundong coal but the utilization of it is limited due to the high alkali metal content which can cause great troubles in a traditional boiler. Supercritical water gasification is a novel thermochemical conversion technique to convert wet feedstock into hydrogen-rich gas product with near zero emission. Reaction kinetics of Zhundong coal gasification in supercritical water was investigated with a quartz reactor in this study. The effects of reaction temperature (650–850 °C) and coal concentration (5–15 wt%) on the gasification behavior were investigated in a wide range of residence time (0–30 min). Experimental results showed that the experimental method employed presents good performance in revealing the continuous change of gas formation with residence time. Carbon gasification efficiency can reach nearly 100% at 850 °C with the residence time of 15 min and the mole fraction of hydrogen was more than 50%. A simplified gasification reaction pathway was also claimed at the end. The results show a promising prospect of Zhundong coal conversion in supercritical water and provide some useful information for reaction kinetics model establishment of coal gasification in supercritical water.